2017
DOI: 10.1007/s00167-017-4472-3
|View full text |Cite
|
Sign up to set email alerts
|

Function and strain of the anterolateral ligament part I: biomechanical analysis

Abstract: This study demonstrated the ALL to be without function under passive motion and with no influence on tibial rotation. On application of extrinsic loads, the ALL had a low but significant stabilizing effect against anterior tibial shear load at low flexion angles. For this reason, it can be concluded that the ALL is supporting the ACL against internal tibial loads to a minor degree. A relationship between the ALL and the pivot shift cannot be concluded. With these results ALL-reconstruction cannot be recommende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 50 publications
1
23
0
10
Order By: Relevance
“…Clási-camente, se pensaba que limitaba la rotación interna en grados cercanos a la extensión (8)(9)(10)16,17) ; sin embargo, otros estudios ponen de manifiesto una limitación rotacional a grados altos de flexión de la rodilla (15,19,21,49) . Dada la importancia del LAL en el control del pivot shift (62)(63)(64)66) , se ha retomado el interés en las reconstrucciones de estas estructuras asociadas a la cirugía del LCA en un intento de disminuir el pivot shift residual y mejorar la estabilidad.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Clási-camente, se pensaba que limitaba la rotación interna en grados cercanos a la extensión (8)(9)(10)16,17) ; sin embargo, otros estudios ponen de manifiesto una limitación rotacional a grados altos de flexión de la rodilla (15,19,21,49) . Dada la importancia del LAL en el control del pivot shift (62)(63)(64)66) , se ha retomado el interés en las reconstrucciones de estas estructuras asociadas a la cirugía del LCA en un intento de disminuir el pivot shift residual y mejorar la estabilidad.…”
Section: Discussionunclassified
“…Los estudios biomecánicos sobre el LAL más recientes ponen de manifiesto el control de la estabilidad rotacional a grandes ángulos de flexión (9,18,20,21,24,(47)(48)(49) , donde no existiría un pivot shift significativo (se explora a unos 30° de flexión), mientras que otros defienden el control del mismo en extensión y escasos ángulos de flexión (1,(8)(9)(10)13,16,17) , con posibilidad de ser apreciado en el pivot shift, siendo un restrictor secundario en la estabilidad anteroposterior.…”
Section: Clínicaunclassified
See 1 more Smart Citation
“…Therefore, ALL reconstruction cannot be recommended at the moment without further biomechanical investigations. 36 From a biomechanical point of view, internal rotation of the knee is better controlled by a lateral extra-articular structure compared to the centrally located ACL because of a longer lever arm. 37,38 Cadaveric studies showed that starting with 30 degrees of flexion, the deep capsulo-osseous fibers of the iliotibial tract play an important role regarding the rotational stability of the knee, while the ALL is just of secondary importance.…”
Section: Functionmentioning
confidence: 99%
“…Los estudios biomecánicos ponen de manifiesto el papel de esta estructura en el control de la estabilidad rotacional, existiendo debate sobre la posición donde se produce mejor función biomecánica por la misma. Parece ser que presenta mayor tensión en grados cercanos a la extensión (1,(8)(9)(10)13,16,17) , pero estudios recientes defienden su control a mayor flexión de rodilla (15,(18)(19)(20)(21) .…”
Section: Introductionunclassified